Expansion of extrafollicular B and T cell subsets in childhood-onset systemic lupus erythematosus - Baxter, Ryan M.; Wang, Christine S.; Garcia-Perez, Josselyn E.; Kong, Daniel S.; Coleman, Brianne M.; Larchenko, Valentyna; Schuyler, Ronald P.; Jackson, Conner; Ghosh, Tusharkanti; Rudra, Pratyaydipta; Paul, Debdas; Claassen, Manfred; et al. (Frontiers in Immunology, 2023)
Most childhood-onset SLE patients (cSLE) develop lupus nephritis (cLN), but only a small proportion achieve complete response to current therapies. The prognosis of children with LN and end-stage renal disease is particularly dire. Mortality rates within the first five years of renal replacement therapy may reach 22%. Thus, there is urgent need to decipher and target immune mechanisms that drive cLN.Despite the clear role of autoantibody production in SLE, targeted B cell therapies such as rituximab (anti-CD20) and belimumab (anti-BAFF) have shown only modest efficacy in cLN. While many studies have linked dysregulation of germinal center formation to SLE pathogenesis, other work supports a role for extrafollicular B cell activation in generation of pathogenic antibody secreting cells. However, whether extrafollicular B cell subsets and their T cell collaborators play a role in specific organ involvement in cLN and/or track with disease activity remains unknown. Using highdimensional phenotypic and functional data in conjunction with unbiased computational analyses, we show that cSLE patients have an extrafollicular B cell expansion signature, with increased frequency of i) DN2 (CD27 -IgD -CXCR5 -CD11c + ), ii) Bnd2 (activated, formerly anergic, CD27 -IgM - IgD + CXCR5 -CD11c + ), iii) plasmablasts, and iv) peripheral T helper cells. Most importantly, we discovered that this extrafollicular signature correlates with disease activity in cLN, supporting extrafollicular T/B interactions as a mechanism underlying pediatric renal pathogenesis.